Analisis Finansial Usahatani Beberapa Jenis Varietas Padi Lokal di Kecamatan Gambut Kabupaten Banjar Kalimantan Selatan - Risna Nadiar; Sadik Ikhsan (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
This research was aimed to determine and to compare farm income and farm profit of some focal paddy varieties (Siam Rukut, Siam Mutiara and Siam unus)and to determine their feasibilities. The results showed that total cost for each variety was Rp 7,228,544 ha' Siam Rukut, RD 7,475,117 ha' Siam Mutiara, and Rp 6,881,529 ha' Siam Unus. Moreover, total revenue for each variety was Rp 14,340,934 ha' Siam Rukut, Rp 16,405,757 ha' Siam Mutiara, and Rp 14,956,400 ha' Siam Unus. Then, farm income was Rp 12,571,854 ha' Siam Rukut, Rp 14,526,345 ha' Siam Mutiara, and Rp 13,171,639 ha' Siam Unus, and farm profit was Rp 7,112,389 ha' Siam Rukut, Rp 8,930,640 ha' Siam Mutiara, and Rp 8,074,870 ha' Siam Unus. Statistically, all these three varieties had the same capacity in generati ng farm income. However, in term of money, Siam Mutiara generated the highest income compared to the others. In addition, paddy farm of these three varieties was feasible, in which Siam Mutiara variety had the highest RCR.